Ulasan masalah dalam implementasi penilaian pembelajaran IPAS untuk mencapai pendidikan pada Kurikulum Merdeka SD/MI - Abidah, Faizah Nurul (Maliki Interdisciplinary Journal, 2025)
Learning evaluation is a crucial element in the educational process. Effective evaluation should provide a clear picture of student achievement, particularly in science and education learning in elementary schools (SD/MI) in accordance with the Independent Curriculum. Considering that the Independent Curriculum requires a shift in perspective in the learning process, its implementation certainly faces various challenges. This study aims to investigate and identify various challenges in implementing science and education learning assessment at the elementary school/MI level. The method used is a literature study. The results of the study indicate that teachers face several obstacles in implementing science and education learning assessment to achieve the educational goals of the Independent Curriculum, including: Not fully understanding the characteristics of each type of assessment, Difficulty in selecting appropriate tools to evaluate competencies based on learning objectives, Difficulty in designing comprehensive assessments, and Challenges in ensuring assessment tools can accommodate differences in student abilities fairly. These problems impact the effective use of time. To overcome these problems, teachers are advised to participate in training to improve their ability to design assessment tools.